Lean readiness assessment model – a tool for Humanitarian Organizations' social and economic sustainability. Issue 2 (20th March 2020) - Shafiq, Muhammad; Soratana, Kullapa
Abstract : Purpose: purpose of this study is to present a Lean Readiness Assessment Model (LRAM) for assessing the readiness of Humanitarian Organizations (HO) for adopting Lean Management (LM) (Johanson et al. ) practices. Literature reveals that implementation of LM itself is a cost and most organizations have failed to adopt LM techniques due to a non-readiness status and a non-supportive organizational culture. This situation indicates that the assessment of organizations' readiness before implementation of lean techniques is necessary. Design/methodology/approach: This was an empirical quantitative study. Based on a synthesis of the literature, a conceptual model was developed by identifying seven critical success factors (CSFs). The CSFs were validated by HO professionals via a questionnaire-based survey. The data from the responses were analysed by applying partial least square structured equation modelling (PLS-SEM) using the SmartPLS3 software. Findings: A proven LRAM was constructed that consists of CSFs (independent and mediating variables), which have reflected positive coefficients and significant t >1.96 and p < 0.05 values. The CSFs that are significant include process management, planning and control management, customer relationship management, human resource management, communication and coordination management and a positive organizational culture. The CSFs of supplier relationship and top management and leadership had insignificant t and p values and were dropped from the final LRAM. Originality/value: This is a unique and rare study in its nature which developed LRAM for HO sector. The contribution of this model is to improve the efficiency and sustainability (economic and social aspects) of an HO under scarce resource conditions.